Stroke Prevention in Atrial Fibrillation - Vinall, Maria (MD Conference Express, 2008)
This article reviews multiple studies that evaluated other pharmacologic agents, as well as discusses three anticoagulation management strategies that can be sued during atrial fibrillation (AF) ablation and methods for assessing and identifying stroke risk in AF patients.